Does Similarity of Local GAAP to U.S. GAAP Explain Analysts' Forecast Accuracy? - Guan, Yuyan (Institutional Knowledge at Singapore Management University, 2006)
This paper examines the relation between analysts’ earnings forecast accuracy and the closeness of local GAAP to US GAAP. We adopt the convergence scores developed in Bradshaw et al. (2004) to measure the closeness between local GAAP and US GAAP. Controlling for other factors that may affect forecast accuracy, we find strong evidence that analysts’ forecasts are more accurate for firms domiciled in a jurisdiction for which the local GAAP is more similar to US GAAP. Moreover, we find that the relation between analysts’ forecast accuracy and proximity of local GAAP to US GAAP varies predictably with both home country disclosure levels and the number of analysts following the firm. Overall, our results indicate that convergence to a high quality international standard (such as US GAAP) can have important economic benefits, but that the importance of the GAAP system is contextual and varies with both institutional and firm-specific factors.